Hospitalizações de idosos por condições sensíveis à atenção primária no Brasil - Fernandes, Sheila Ferreira (2015)
Introduction: The focus was an increase in the elderly population in Brazil and worldwide. Hospitalizations in the elderly are the most costly part representatively in the population of Brazil. In 2011, Brazil spent about 3.3 billion reais in hospitalizations for this age group, which accounts for about 30% of the total amount spent for about 10% of the population. One way to reduce these costs would be avoiding hospitalizations for sensitive conditions primary care (HSCPC) health through the expansion of the Family Health Strategy (FHS). To evaluate the relationship between HSCPC in the elderly and the FHS coverage in Brazil from 2003, 2008 and 2013. And also identify potential variables that influence these admissions. Methods: Through the DATASUS database and Hospital Information System of the Unified Health System (SIH / SUS), was evaluated by linear regression, the relationship between HSCPC rate and FHS coverage in all UF in over 60 in the periods in question. They also analyzed the specific causes of hospitalizations in the elderly and its association with the Human Development Index (HDI) and the Gini coefficient of each state. Results: There was no significant association between the percentage of HSCPC and the FHS coverage percentage in periods. Some diseases, like diabetes and heart failure, tended to reduce these periods, but this was not statistically significant. However, we found an inverse relationship of HSCPC and the human development index of each state and not with the Gini coefficient. Conclusion: The results of this study need to be improved, since the extensive diversity of our country and their conditions of access to outpatient and inpatient health. The HSCPC seem to be related to a broader context of the health-disease that can be represented by the human development index in UF Brazil.